KAJIAN PENERAPAN SISTEM INFORMASI KARYAWAN BERBASIS WEB BERDASARKAN PENDEKATAN TAM - Mochamad Wahyudi (LPPM Universitas Bina Sarana Informatika, 2009)
The purposes of this study are to find the dominant factors which correlate and influence the level of technology acceptance, particularly Web-Based Employee Information System to its end users, of which are the employees of Bina sarana Informatika (BSI), and to know how an accepted model of new technology in a form of Web-Based Employee Information System is emplemented in a tertiary education institution.The Web-Based Employee Information System used in this study is one of information systems implemented by BSI, all of which were web-based designed that require an internet browser, such as: Internet Explorer or Mozilla Firefox. It is computer-accessible to employees both from within or outside BSI campus since the system is connected with local computer network via both intranet as well as internet facilities. This Web-based Employee Information System, which is stored in a webserver of the Internet, has a domain address “bsi.ac.id” and it is accessible via BSI website at http://www.bsi.ac.id. Some facilities available are: employee data processing, academic service, prospective students information, courses and programs, Jabatan Fungsional Dosen.The instrument for this study is questioner with Semantic Differential Scale ranging from 1 to 7, representing answers ranging from ‘extremely disagree’ to ‘extremely agree’. This study also makes use of both Technology Accepted Model (TAM) to describe the relationship between factors influencing the use of Web-Base Employee Information System and Structural Equation Modelling (SEM) to analyse data. The software used are AMOS and SPSS for Mindows 16.0.1 version.The result of this study is useful for identifying and putting in mind the role of Web-Based Employee Information System, which is accessible at http://www.bsi.ac.id, as a facility to support employees’ working accomplishment.Key words : Web-Based Employee Information System, Technology Accepted Model (TAM), Structural Equations Modelling (SEM), Analysis of MOment Structure (AMOS)